The Impact of GLP-1 Analogues and Tirzepatide on Female Fertility: Mechanisms, Clinical Evidence, and Implications - Niwińska, Klaudia Elżbieta; Borowski, Michał; Leśniak, Julia Aleksandra; Leśniak, Natalia Maria; Patrzykąt, Klaudia Martyna; Zakrzewska, Anna Maria; Popielarska, Kinga; Michalak, Julia Agnieszka; Augustyn, Monika; Midera, Aleksander (Journal of Education, Health and Sport, 2026)
Obesity impairs female fertility through metabolic, endocrine and inflammatory pathways that disrupt ovulation, reduce oocyte competence and impair endometrial receptivity. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and the dual glucose-dependent insulinotropic polypeptide (GIP)/GLP-1 receptor agonist tirzepatide have become highly effective therapies for weight management and metabolic optimisation, raising interest in their potential reproductive benefits. This narrative review synthesises current mechanistic and clinical evidence on how GLP-1 receptor agonists and tirzepatide may influence reproductive function in women of reproductive age. A literature search was conducted using PubMed, Scopus and Web of Science for peer-reviewed human studies and major reviews published up to December 2025 that evaluated metabolic, endocrine or reproductive outcomes. Available evidence suggests that GLP-1 signalling may influence the hypothalamic–pituitary–ovarian axis, adipokine pathways, oocyte mitochondrial function and endometrial gene expression. Clinical studies indicate that liraglutide and semaglutide improve body weight, insulin resistance and hyperandrogenism, leading to restoration of menstrual regularity and increased ovulation rates, with some reports of improved spontaneous conception and assisted reproduction outcomes. Tirzepatide provides greater metabolic benefits, although fertility-specific data remain limited. Overall, GLP-1–based therapies act primarily as metabolic optimisers that may secondarily enhance fertility, while evidence for direct reproductive effects and periconceptional safety remains insufficient.